AC vs. DC Distribution Efficiency: Are We on the Right Path? - Hasan Erteza Gelani; Faizan Dastgeer; Mashood Nasir; Sidra Khan; Josep M. Guerrero (Energies, 2021)
The concept of DC power distribution has gained interest within the research community in the past years, especially due to the rapid prevalence of solar PVs as a tool for distributed generation in DC microgrids. Various efficiency analyses have been presented for the DC distribution paradigm, in comparison to the AC counterpart, considering a variety of scenarios. However, even after a number of such comparative efficiency studies, there seems to be a disparity in the results of research efforts, wherein a definite verdict is still unavailable. Is DC distribution a more efficient choice as compared to the conventional AC system? A final verdict is absent primarily due to conflicting results. In this regard, system modeling and the assumptions made in different studies play a significant role in affecting the results of the study. The current paper is an attempt to critically observe the modeling and assumptions used in the efficiency studies related to the DC distribution system. Several research efforts are analyzed for their approach toward the system upon which they have performed efficiency studies. Subsequently, the paper proposes a model that may alleviate the shortcomings in earlier research efforts and be able to give a definite verdict regarding the comparative efficiency of DC and AC networks for residential power distribution.